Mental Existence Debates in the Post-Classical Period: A Study in the Context of the Essence and Category of Knowledge - Murat Kaş (Nazariyat: Journal for the History of Islamic Philosophy and Sciences)
The debates on the idea of mental existence is one of the issues in which the tension between the basic principles of Avicennian ontology and his epistemology is most evident. The question of mental existence, which developed into a problématique as a result of Fakhr al- Dīn al-Rāzī’s efforts to trace Avicennian philosophy’s intimations, possessed a character that expanded through different prospects and perspectives following both the arguments advanced in support of this idea and the major challenges that the Avicennian theory of perception and knowledge met. It thus became a target for criticism in due course. This study takes as its subject matter the most significant criticism against the idea of mental existence and the perspectives that attempt to settle the ensuing problem in this context. This particular criticism and the pursuit of a solution is a notable part of the mental existence debates that were current from the thirteenth to the nineteenth centuries. The criticism mainly concerns the tension between the mental form as knowledge and its equivalence with the external object in terms of essence. Accordingly, mental form is a knowledge and an accident in the category of quality. If the object of perception is a substance and the mental image is its equivalent in essence, then the mental image also has to be a substance, which requires the form to be both a substance and an accident. This article, which pursues the trail of the mental existence debate by means of this criticism, tackles the following matters: (i) the media and channels that conveyed the mental existence debate that took shape after al-Rāzī'’s interventions, (ii) the nature of the relation between knowledge and mental existence, and (iii) those suggestions that address the criticism and solutions concerning the category of knowledge.